Modelling the effect of temperament on BMI through appetite reactivity and self-regulation in eating: a Structural Equation Modelling approach in young adolescents - Godefroy, V; Trinchera, L; Romo, L; Rigal, N (International Journal of Obesity, 2016)
Background/Objective: Appetitive traits and general temperament traits have both been correlated with adiposity and obesity in children. However, very few studies have tested structural models to identify the links between temperament, appetitive traits and adiposity in children. A validated structural model would help suggesting mechanisms to explain the impact of temperament on body mass index (BMI). In this study, we used Rothbart’s heuristic definition of temperament as a starting point to define four appetitive traits, including two appetite reactivity dimensions (Appetite Arousal and Appetite Persistence) and two dimensions of self-regulation in eating (Self-regulation In Eating Without Hunger and Self-regulation in Eating Speed). We conducted a cross-sectional study in young adolescents to validate a structural model including these four appetitive traits, Effortful Control (a general temperament trait) and adiposity. Subjects/Methods: A questionnaire assessing the four appetitive trait dimensions and Effortful Control was completed by adolescents from 10 to 14 years old ( n =475), and their BMI-for-age was calculated ( n =441). In total, 74% of the study participants were normal weight, 26% were overweight and 8% were obese. We then used structural equation modelling to test the structural model. Results: We identified a well-fitting structural model (Comparative Fit Index=0.91; Root Mean Square Error of Approximation=0.04) that supports the hypothesis that Effortful Control impacts both dimensions of self-regulation in eating, which in turn are linked with both appetite reactivity dimensions. Moreover, Appetite Persistence is the only appetitive trait that was significantly related to adiposity ( B =0.12; P <0.05). Conclusions: Our model shows that Effortful Control is related to adiposity through the mediation of an individual’s ‘eating temperament’ (appetite reactivity and self-regulation in eating). Results suggest that young adolescents who exhibit high appetite reactivity but a low level of self-regulation in eating are at higher risk for excess adiposity.